(3Yjhf GdfUhUs
(3ChdgG (B:s
(3hHYO aGdQhGjGJ GdhGQOI aj GdfUhU Ydi GdCFeI Ydjge GdSdGe cKjQI ef LgI CUMGH QShd Gddg Udi Gddg Ydjg hBdg hSde GdeYQajf eKd YHOGddg Hf GdYHGS hYHOGddg Hf eSYhO s
(3BNQgG (B:s
(3Yf hVY CMGOjK dcf jZGdWh GdfGS hojTcchge aj CeQ gDdGA GdCFeI gPG eeG dGjLhR aj GdYbd hdGjUM aj ehGVY cKjQI hGdMeO ddg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs